CONGENITAL UMBILICAL DEFECT WITH INTESTINAL EVISCERATION IN A CALF AND ITS SURGICAL MANAGEMENT - Das, JayaKrushna; Behra, Sidhartha Sankar; Senapati, Manas Ranjan; Hembram, Ananta; Behra, Monalisa (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A defect resulting from faulty closure of abdominal wall along its ventral midline called eventration of abdominal viscera which occurred more often in the females than the males (Gahlod et al., 2008). Improper closure of the umbilical opening at birth or hypoplasia of abdominal muscles may result in permanent wall defect and lead to protrusion of internal visceral organs (Sharda et al., 2012). This paper presents a case of congenital intestinal prolapse through the defect in umbilicus of a calf and its surgical correction.